A mixed method study into obstetric sonographer-led-discharge and other forms of sonographer role extension. (August 2022) - Kettlewell, LS; Richards, SP
Introduction: Sonographer-led-discharge was proposed in a maternity unit to provide a holistic service, cut waiting times, ease staffing pressures and increase job satisfaction. This study explored sonographers' experiences and perspectives of this new extended role and other areas of non-obstetric role extension. Understanding these will inform future practice and the success of the proposed obstetric sonographer-led-discharge and career structure. Methods: A mixed methodology, cross-sectional study was performed, with a purposive, non-probability sample using an online data collection tool. The data were analysed using descriptive statistics and thematic analysis. Results: In total, 93 sonographers participated in the study. Of these, 25% of sonographers currently practising obstetric ultrasound said they would not undertake the proposed obstetric sonographer-led-discharge role extension although 90% of the participants said role extension provides job satisfaction. Several themes emerged from the data, including job satisfaction, benefits to the hospital, improved patient pathway, time, personal factors, litigation and intra- and interprofessional resistance. A total of 54% of staff currently performing a role extension have experienced either inter- or intraprofessional conflict and only 48.5% said their workload was manageable. Conclusions: The data collected suggested that, with training and support, the proposed obstetric sonographer-led-discharge role is an appropriate role extension for sonographers. These findings support the premise of the proposed sonographic career structure, although the inter- and intraprofessional resistance identified in the study could form a significant barrier if it is not appropriately considered and managed.